If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-(2x+8)=2x-21
We move all terms to the left:
3x-(2x+8)-(2x-21)=0
We get rid of parentheses
3x-2x-2x-8+21=0
We add all the numbers together, and all the variables
-1x+13=0
We move all terms containing x to the left, all other terms to the right
-x=-13
x=-13/-1
x=+13
| 23x+3=118 | | 4x-8-24+15=42 | | -7v+6(1+8v)=199 | | 65=-1+22x | | a+13.4=28.9 | | 7x-10=4x-29=5x-9 | | 8(2–t)=-4t | | -(x-9)+4=-23+x | | 3x-4-2x+8=13 | | x-9x=5 | | 12(3x+8)=114 | | (2x+3)+(5x+4)=(3x+6)+2x+9 | | 13.4+28.9=a | | 3+9n=5n+3 | | 3v=2v+5 | | 7z+16=13z+4 | | 3k+9=3k+3 | | 2x+7(3x-5)=12 | | n2=-4n | | 5x–3+2x=18 | | n÷2÷4=2 | | -7(x-3)=11-7x | | 2(3x-7)+6(x-5)=-3(3-5x)+5x-21 | | (n+2)(n-1)=0 | | -5(1-2k)-6k=-8+5k | | 2/9j=6 | | -8-7x=74 | | 4n-3(n+2)=-4 | | 8=(3/4)1a+12-1a+4 | | (x-x/x)*x=10 | | 3(2d-24)=11d-18(d-3) | | -24x-3=2x-18 |